Efektivitas Program Pencatatan Akta Kematian pada Dinas Kependudukan dan Pencatatan Sipil Kota Tangerang Selatan - Ashira Salwa Bita; Mawar Mawar (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2024)
A death certificate is proof of a person's death, but in its implementation there are still several problems, including that there are still people who have died but are included in the permanent voter list for the 2024 election and there are falsification of death certificates. The aim of this research is to find out and analyze the effectiveness of the death certificate recording program in the population and civil registration services of South Tangerang City. The method used in this research is a qualitative approach with descriptive methods. The results of the research show that target accuracy is said to be optimal, because people already know and receive death certificate registration services. The program socialization indicators are not yet optimal, because there are still people in the South Tangerang City area who do not know how important it is to take care of population administration, especially death certificates, due to the lack of socialization by the population and civil registration services. In terms of indicators of achieving program objectives, there are still people who have not registered death certificates even though they are aware of the existence of the death certificate registration program. In terms of monitoring indicators, the program has not gone well in its implementation because it was found that people had not registered death certificates, this is because the supervision carried out by the population and civil registration services did not reach enough and was not evenly distributed to all communities in South Tangerang City.